Salvation as healing? : an analysis of Jesse Mugambi and Mercy Oduyoye’s soteriologies in the context of African prosperity gospels - Umaru, Kefas K. (Stellenbosch University, 2017)
This thesis is a study of the doctrine of salvation with particular reference to therapeutic interpretations. Discourses about salvation often center on that which comes in the hereafter, with less emphasis on the here–and-now dimensions of salvation, which has resulted in disparities in the interpretation of salvation within Christian theology. One of these divisions come from circles that embrace the gospel of prosperity, which focuses on wealth and health as proof of salvation, which is irreconcilable with the life experiences of some believers. Therefore, it has become of the utmost importance that salvation is understood properly and more broadly to bringing clarity and avoid such disparities. With a view to presenting a farreaching perspective on salvation, the current study critically investigates the notable works of two African theologians selected from many others, whose scholarly contributions to African Christian theology in general, and salvation in particular, have been remarkable. Chapter One sets out the background to the study and introduces certain concepts that are central to the study, so as to allow coherence in the rest of the thesis. Salvation is one of the essential Christain doctrines, but misconceptions in this regard have made it difficult to ascertain or to articulate its meaning appropriately. The previous view gave rise to different ways of explaining salvation, particularly within circles that embrace the gospel of prosperity, which sees health and wealth as proof of salvation. Unfortunately, no matter how important those forms of salvation are, many believers who have experienced salvation are not wealthy and do not enjoy good health. The above perspective calls for an integrative engagement with other theologians so as to present a balanced and broader view of salvation. For the purpose of considering salvation through a much wider lens, Jesse Mugambi’s and Mercy Oduyoye’s interpretations of salvation are examined in chapters 3 and four respectively. Mugambi is a Kenyan Anglican theologian whose salvific quest centres on reconstruction as a paradigm that befits Africa in the 21st century – rather than liberation, which has often been the norm. He discusses reconstruction as a form of salvation that covers social and structural dimensions, thereby presenting an understanding of salvation that is much broader than restricting it to either salvation from sin or the acquisition of wealth and health. Oduyoye is a Ghanian Methodist theologian who focuses her research work on the well-being of women and children in particular, but also that of society. Her research concerns more than the human quest for well-being – also that of society, with particular attention to justice and equality. Shaping an enabling society where individuals are acceptedand treated with dignity would go a long way to healing many of humanity’s problems, particularly those experienced by women and children, which is considered to be a form of salvation in the context of this study. Chapter 5 draws some conclusions from the preceding chapters and suggests three models for a therapeutic interpretation of salvation, namely reconciliation, transformation, and empowerment. Concerning the prosperity gospel’s perception of salvation and that of Mugambi and Oduyoye, the study concludes that none of those approaches is wrong in itself, but all could offer a better interpretation of salvation by including other perceptions. The study suggests that none of the approaches should be followed exclusively without including others. Integration would afford a balanced view of salvation that comprises different facets of life with particular reference to the therapeutic sense. In that way, the disparity in understanding salvation can be bridged.
free